Isoliquiritigenin Attenuates Staphylococcus aureus Adhesion and Invasion to Counteract Staphylococcus aureus Pathogenicity and Infection - Tian, Lili; Sun, Jian; Jiang, Hong; Wang, Hongjun; Zheng, Jian; Wang, Dacheng; Zhang, Libo (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMethicillin-resistant Staphylococcus aureus (MRSA) is a major clinical challenge due to its virulence and multidrug resistance. Antivirulence strategies targeting key pathogenic mechanisms without affecting bacterial viability provide a promising alternative to conventional antibiotics.MethodsThe inhibitory effect of isoliquiritigenin (ISL) on S. aureus sortase A (SrtA) was assessed using a fluorescence resonance energy transfer assay. Fluorescence quenching and molecular docking analyses were performed to elucidate the binding interaction between ISL and SrtA. Adhesion and biofilm formation were evaluated on fibrinogen- and fibronectin-coated surfaces, and bacterial growth was monitored to confirm non-bactericidal activity. The therapeutic efficacy of ISL was further examined in a murine pneumonia model through bacterial load quantification, histopathological analysis, and survival evaluation.ResultsISL inhibited SrtA activity in a dose-dependent manner (IC50 = 13.34 µg/mL), disrupted adhesion and biofilm formation without affecting bacterial growth, and bound reversibly to key catalytic residues of SrtA. In vivo, ISL treatment significantly reduced pulmonary bacterial burden, alleviated tissue damage, and improved survival in infected mice.DiscussionISL effectively attenuates MRSA pathogenicity by targeting SrtA-mediated virulence rather than bacterial viability. These results highlight ISL as a promising antivirulence agent and a potential adjuvant for combating antibiotic-resistant S. aureus infections.